Current trends in antiviral drug development - De Clercq, Erik (Henry Stewart Talks, 2013)
Chemotherapy of virus infections, AIDS, and malignant diseases, Molecular mechanism of action & enzyme targets of antiviral and antitumor agents, Nucleoside and nucleotide analogues, Reverse transcriptase inhibitors, Virus adsorption, fusion and uncoating inhibitors